2012
DOI: 10.1186/1471-2407-12-87
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis intestinalis and portal venous gas secondary to Gefitinib therapy for lung adenocarcinoma

Abstract: BackgroundPneumatosis intestinalis (PI), defined as the presence of gas in the bowel wall, and portal venous gas (PVG) are relatively rare radiological findings. Although several chemotherapeutic agents and anti-vascular endothelial growth factor agents are reported to be associated with PI and PVG, an association with anti-epidermal growth factor receptor (EGFR) agents has not been described previously.Case presentationThe present report describes a case of PI and PVG secondary to treatment with an EGFR tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Although the pathogenesis has not been fully established, various causes or clinical situations have been suggested to explain the development of PCI. They are classified as the following categories [ 1 , 2 , 7 10 ]: (1) mechanical irritation or increased intra-abdominal pressure caused by surgery, trauma, or colonoscopy that causes intraluminal air to penetrate into the bowel wall; (2) respiratory disease such as chronic obstructive pulmonary disease can result in pneumomediastinum by increased pulmonary alveolar pressure and rupture, and the trapped air can move into the abdominal cavity; (3) bacterial overgrowth in the lumen can cause increased intraluminal gas and pressure to penetrate through a disrupted or damaged mucosal barrier; (4) Disequilibrium of luminal gas composition and pressure causing supersaturation of gas, and resultantly forming air bubbles in the wall along with the bowel vasculatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenesis has not been fully established, various causes or clinical situations have been suggested to explain the development of PCI. They are classified as the following categories [ 1 , 2 , 7 10 ]: (1) mechanical irritation or increased intra-abdominal pressure caused by surgery, trauma, or colonoscopy that causes intraluminal air to penetrate into the bowel wall; (2) respiratory disease such as chronic obstructive pulmonary disease can result in pneumomediastinum by increased pulmonary alveolar pressure and rupture, and the trapped air can move into the abdominal cavity; (3) bacterial overgrowth in the lumen can cause increased intraluminal gas and pressure to penetrate through a disrupted or damaged mucosal barrier; (4) Disequilibrium of luminal gas composition and pressure causing supersaturation of gas, and resultantly forming air bubbles in the wall along with the bowel vasculatures.…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients have related symptoms, conservative management including fasting, parenteral nutrition, or intestinal decompression is sufficient, with excellent prognosis. Occasionally, portal venous gas can be noted on CT findings in cases of mesenteric ischemia, and surgery may be considered if frank bowel infarction is suspected [ 7 ]. Based on such clinical knowledge, our patient was closely observed with conservative management and recovered in 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of gas in the portal venous system was generally considered to be a serious intra-abdominal event, many benign cases have been put forward with the development of imaging modalities. Our search for reported cases of HPVG during the most recent 5 years (table 2 ) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] revealed that 20 of the 31 patients were treated by a nonsurgical approach, and 22 (71%) of the 31 patients recovered, suggesting that HPVG is not always a fatal sign in those patients. In addition, invasive therapy, including chemotherapy, endoscopic retrograde cholangiopancreatography, and CT-guided aspiration biopsy, was performed in 14 (45.2%) of the 31 patients before onset of HPVG.…”
Section: Discussionmentioning
confidence: 99%
“…Although gefitinib is generally well tolerated, its most commonly reported toxicities concern the gastrointestinal tract (diarrhea, nausea, and vomiting) and skin (rash, acne, dry skin, and pruritus). Severe gastrointestinal toxicity caused by gefitinib is uncommon, and only 1 % of patients receiving gefitinib therapy develop grade 3 or 4 diarrhea [ 9 , 13 ]. To the best of our knowledge, only a few studies, including the current case report, have reported the association between PI and gefitinib [ 8 , 9 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Recently, molecular-targeted drugs have been shown to cause gastrointestinal toxicity, including PI perforation, enteritis, and fistula formation [ 1 , 4 6 ]. Anti-epidermal growth factor receptors such as cetuximab and erlotinib have been reported to be associated with PI; however, only a few cases have been reported in association with gefitinib treatment [ 1 , 7 9 ]. This is a report of PI associated with gefitinib therapy.…”
Section: Introductionmentioning
confidence: 99%